2015
DOI: 10.1007/s00264-015-2837-0
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic assessment in simulated operative positions before knee arthroplasty can be useful in deep vein thrombosis prediction

Abstract: We believe that preoperative ultrasound analysis performed during the simulation of operative positions is a useful pre-operative test that can identify patients at risk of developing postoperative DVT. We would recommend that during surgery procedure to minimise forced position of knee flexion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Total knee arthroplasty (TKA): A Doppler ultrasound study conducted intraoperatively before a TKA procedure found that calf venous blood flow was significantly reduced with knee flexion of at least 90 o , and that postoperative DVT (especially proximal DVT) occurred more commonly in patients with the lowest preoperative venous flow velocity after knee flexion 564 . The authors concluded that marked knee flexion during TKA reduced venous blood flow and may have increased DVT risk.…”
Section: - Does the Intra-operative Positioning Of A Patient Undergoi...mentioning
confidence: 99%
“…Total knee arthroplasty (TKA): A Doppler ultrasound study conducted intraoperatively before a TKA procedure found that calf venous blood flow was significantly reduced with knee flexion of at least 90 o , and that postoperative DVT (especially proximal DVT) occurred more commonly in patients with the lowest preoperative venous flow velocity after knee flexion 564 . The authors concluded that marked knee flexion during TKA reduced venous blood flow and may have increased DVT risk.…”
Section: - Does the Intra-operative Positioning Of A Patient Undergoi...mentioning
confidence: 99%
“…Wensing at al 18 reported magnetic resonance angiographic findings of age-related conformational change from smooth curvature at lower knee flexion angles to relative tortuosity at higher flexion angles for the popliteal artery and stated their concern for a comparable deformity of the popliteal vein by anatomical association. Hadžimehmedagić et al 7 demonstrated that the deep knee flexion angles required to perform total knee arthroplasty caused a disproportionate obstruction to popliteal venous flow through the tibial vein and hypothesized a vessel deformation mechanism at this extreme angle.…”
Section: Discussionmentioning
confidence: 99%
“…4-6 Beyond 30° to 60° of knee flexion, however, venous flow obstruction again increases in relation to the degree of flexion, exhibiting a large effect size. 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation